2013
DOI: 10.11622/smedj.2013170
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self-harm in adolescent psychiatric outpatients in Singapore: prevalence and associated risk factors

Abstract: DSH is a significant clinical problem that may be influenced by biological and clinical factors. Adolescents presenting with DSH should be examined for mood and alcohol use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
2
5
1
Order By: Relevance
“…The prevalence of DSH in this study (23.1%) was similar to an earlier study in Singapore [ 18 ]. The consistency in this finding, in addition to the sizeable number of patients involved and the equal gender proportion in the current sample, contributes to the accuracy in estimating prevalence.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of DSH in this study (23.1%) was similar to an earlier study in Singapore [ 18 ]. The consistency in this finding, in addition to the sizeable number of patients involved and the equal gender proportion in the current sample, contributes to the accuracy in estimating prevalence.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the gender patterns reported in Western samples, adolescent females were also found to have significantly higher rates of DSH than adolescent males in Singapore [ 18 ], Japan [ 22 ] and Hong Kong [ 23 , 24 ]. In Singapore, one published study reported that 23.6% of adolescent patients at a psychiatric outpatient clinic engaged in DSH, and DSH was associated with female gender, mood disorders, adjustment disorders and alcohol use [ 18 ]. However, the authors did not examine the different types of DSH behaviours engaged and did not account for variables such as history of abuse and forensic history.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, NSSI in outpatient adolescent children of PTSD male veterans may represent an attempt to express dissatisfaction with current environmental circumstances or solicit assistance from others. The prevalence of NSSI found in this study was higher in comparison with that in other studies reporting NSSI among adolescents in outpatient setting (Díaz de Neira et al, 2013;Esposito-Smythers et al, 2010;Loh, Teo, & Lim, 2013). This discrepancy might be explained by different cultural background factors in Croatia or it might possibly be an indicator for the increased incidence of NSSI among adolescent children of PTSD male veterans.…”
Section: Discussioncontrasting
confidence: 95%
“…Brunner and colleagues [ 54 ] recently reported an obvious association between adolescent smoking and direct self-injurious behavior (D-SIB). Others, however, ascertained no significant association between smoking and SIB in both genders [ 52 ] or at least in boys [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%